Twitter Analytics to Inform Provisional Guidance for COVID-19 Challenges in the Meatpacking Industry. Issue 4 (25th January 2021) - Durand-Moreau, Quentin; Mackenzie, Graham; Adisesh, Anil; Straube, Sebastian; Chan, Xin Hui S; Zelyas, Nathan; Greenhalgh, Trisha
Abstract: The COVID-19 pandemic raised considerable challenges to obtain reliable guidance to help occupational health practitioners, workers, and stakeholders building up efficient prevention strategies at the workplace, between the constant increase of publications in the domain, the time required to run high-quality research and systematic reviews, and the urgent need to identify areas for prevention at the workplace. Social Media and Twitter, in particular, have already been used in research and constitute a useful source of information to identify community needs and topics of interest for prevention in the meatpacking industry. In this commentary, we introduce the methods and tools we used to screen relevant posts on Twitter. Twitter analytics is a way to capture real-time concerns of the community and help ensure compliance with the notion of social accountability. As such research has limitations in terms of exhaustiveness and level of evidence, it should be considered as provisional guidance to direct both actions at the workplace and further conventional research projects.